2015
DOI: 10.4049/jimmunol.1402481
|View full text |Cite
|
Sign up to set email alerts
|

TLR Signaling Modulates Side Effects of Anticancer Therapy in the Small Intestine

Abstract: Intestinal mucositis represents the most common complication of intensive chemotherapy, which has a severe adverse impact on quality of life of cancer patients. However, the precise pathophysiology remains to be clarified and there is so far no successful therapeutic intervention. Here, we investigated the role of innate immunity through TLR signaling in modulating genotoxic chemotherapy-induced small intestinal injury in vitro and in vivo. Genetic deletion of TLR2, but not MD-2, in mice resulted in severe che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 71 publications
2
76
0
Order By: Relevance
“…Similar results have also been demonstrated in methotrexate-induced gut toxicity, with MD-2 (TLR4 accessory protein) deletion improving clinical and histological parameters of toxicity (36). Importantly, this study showed that TLR4 and TLR2 appear to have opposing roles, with both genetic deletion and pharmacological inhibition of TLR2 worsening methotrexate-induced damage (36). It appears that TLR2 has paradoxical roles in chemotherapy-induced gut toxicity, with improvements seen in Tlr2 -/-mice treated with irinotecan.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Similar results have also been demonstrated in methotrexate-induced gut toxicity, with MD-2 (TLR4 accessory protein) deletion improving clinical and histological parameters of toxicity (36). Importantly, this study showed that TLR4 and TLR2 appear to have opposing roles, with both genetic deletion and pharmacological inhibition of TLR2 worsening methotrexate-induced damage (36). It appears that TLR2 has paradoxical roles in chemotherapy-induced gut toxicity, with improvements seen in Tlr2 -/-mice treated with irinotecan.…”
Section: Discussionsupporting
confidence: 69%
“…For example, significant improvements in acute inflammation have been shown in the absence of TLR4 and MyD88, a downstream signaling molecule of TLR, following acute infection with Citrobacter rodentium (35). Similar results have also been demonstrated in methotrexate-induced gut toxicity, with MD-2 (TLR4 accessory protein) deletion improving clinical and histological parameters of toxicity (36). Importantly, this study showed that TLR4 and TLR2 appear to have opposing roles, with both genetic deletion and pharmacological inhibition of TLR2 worsening methotrexate-induced damage (36).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Recently, TLR/MyD88/NF-κB pathway has been implicated in the mechanisms of damage involved in chemotherapy-related GIM (27). It has also been reported that TLR-2 acts as a central regulator of xenobiotic defense and targeting TLR2 may represent a novel therapeutic approach in chemotherapy-induced GIM (26).…”
Section: Pathobiology Of Gimmentioning
confidence: 99%
“…These overlapping steps are thought to be largely driven by the activation of NFκB, subsequently promoting key pro-inflammatory cytokines. Furthermore, apoptosis, pathogenic bacteria, inflammation, matrix metalloproteinases (MMPs), loss of mucosal barrier integrity and toll like receptors (TLRs) have also been reported to play an important role in GIM (21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Pathobiology Of Gimmentioning
confidence: 99%